POLITICAL COMMUNICATION STRATEGY OF THE PDIP DISTRICT BRANCH IN KEPULAUAN SERIBU FOR THE REGIONAL HEAD ELECTIONS (PILKADA) 2024 - Herlina Muzanah Zain; Sofi Rama Riyansyah; Dejehave al Jannah (Jurnal Administrasi Publik, 2025)
This study is motivated by the challenges of political communication during local elections (Pilkada) in archipelagic regions with distinct geographical and social characteristics, such as the Thousand Islands (Kepulauan Seribu). The central problem explored is how the Indonesian Democratic Party of Struggle (PDI Perjuangan) designed and implemented a communication strategy that effectively adapted to the local context. The objective of this research is to analyze the contextual communication strategy and assess its effectiveness in building political trust and engagement in a marginalized island setting. This study employs a descriptive qualitative approach, using interviews, observations, and literature review as data collection techniques. Theoretical grounding is provided by political communication and strategic communication concepts, including communicator, message, medium, audience, as well as segmentation, positioning, and branding. The findings reveal that PDI Perjuang an utilized a hybrid strategy that combines face-to-face interaction and digital communication, reinforced by community-based outreach, involvement of local figures, and the use of culturally resonant symbols. Unlike most prior research that centers on urban or mainland political dynamics, this study offers a unique contribution by focusing on the adaptation of political communication strategies in geographically isolated and socially cohesive island communities. The originality of this study lies in its emphasis on the effectiveness of localized communication approaches in areas often overlooked in mainstream electoral research.